From Automated Synthesis to In Vivo Application in Multiple Types of Cancer-Clinical Results with [68Ga]Ga-DATA5m.SA.FAPi - Lukas Greifenstein; Carsten S. Kramer; Euy Sung Moon; Frank Rösch; Andre Klega; Christian Landvogt; Corinna Müller; Richard P. Baum (MDPI AG, 2022)
Radiolabeled FAPI (fibroblast activation protein inhibitors) recently gained attention as widely applicable imaging and potential therapeutic compounds targeting CAF (cancer-associated fibroblasts) or DAF (disease-associated fibroblasts in benign disorders). Moreover, the use of FAPI has distinct advantages compared to FDG (e.g., increased sensitivity in regions with high glucose metabolism, no need for fasting, and rapid imaging). In this study, we wanted to evaluate the radiochemical synthesis and the clinical properties of the new CAF-targeting tracer [68Ga]Ga-DATA5m.SA.FAPi. The compound consists of a (radio)chemically easy to use hybrid chelate DATA.SA, which can be labeled at low temperatures, making it an interesting molecule for 'instant kit-type' labeling, and a squaric acid moiety that provides distinct advantages for synthesis and radiolabeling. Our work demonstrates that automatic synthesis of the FAP inhibitor [68Ga]Ga-DATA5m.SA.FAPi is feasible and reproducible, providing convenient access to this new hybrid chelator-based tracer. Our studies demonstrated the diagnostic usability of [68Ga]Ga-DATA5m.SA.FAPi for the unambiguous detection of cancer-associated fibroblasts of various carcinomas and their metastases (NSCLC, liposarcoma, parotid tumors, prostate cancer, and pancreas adenocarcinoma), while physiological uptake in brain, liver, intestine, bone, and lungs was very low.